Thanatophoric Dysplasia - Badal, Sachendra; Roy, Shuvendu; Singh, Daljit (Journal of Nepal Paediatric Society, 2016)
Thanatophoric Dysplasia (TD) is a severe skeletal dysplasia that is lethal in the neonatal period. There are two defined TD subtypes which have been classified clinically. The incidence is approximately 1/20,000 to 1/50,000. Type I TD being more frequent than Type II. Most individuals with TD die within the first few hours.This condition has characteristic sonographic features detected antenatally by midgestation, although distinction from other short-limbed dysplasia syndromes may be difficult. We report a case of type I TD with typical clinicoradiological features who succumbed within one hour of life. J Nepal Paediatr Soc 2015;35(3):304-306.